Aspek Hukum Perkawinan Adat di Tulang Bawang Antara Tradisi dan Modernitas - Feren Vexia; Zainudin Hasan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Traditional marriage in Tulang Bawang is not merely regarded as the union of two individuals, but also as a reflection of the cultural values and collective identity of the Lampung community. Amid the forces of modernization and the implementation of national law, this tradition faces challenges to remain preserved without losing its essential meaning. This study explores the legal values embedded in the customary marriage practices of Tulang Bawang and examines how these traditions adapt to Indonesia’s legal framework, particularly as stipulated in Law No. 1 of 1974 concerning Marriage. Employing a qualitative approach that combines legal analysis and social perspectives, the findings reveal that the people of Tulang Bawang strive to maintain a balance between preserving their customary traditions and complying with state law. The community continues to uphold ancestral heritage while remaining open to progressive change. The harmony between customary law and modern law demonstrates that both can coexist and complement one another, creating a meaningful dialogue between the values of the past and the realities of the present.